A review on current status of traditional uses, phytochemistry, pharmacology and conservation of Inula racemosa Hook. f. (2022) - Jaiswal, Riya; Mutreja, Vishal; Singh Sohal, Harvinder; Sharma, Ajay
Highlights: Inula racemosa is also known as Pushkarmool, and is mainly found in Western Himalayas desert regions. Inula racemosa is a critically endangered plant. Traditionally, it is used to cure skin diseases, abdominal pain, diabetes, cough, teeth problems, etc. I. racemosa also shows wide range of pharmacological activities. I. racemosa contains novel secondary metabolites. Abstract: From ancient times, therapeutic herbal plants are extensively utilized in various traditional medicine practices. One such plant is Inula racemosa Hook. f., which is also known as Puskarmool. I. racemosa is mainly found in India's temperate and sub-alpine regions particularly in Kashmir, Himachal Pradesh, and Uttarakhand. Different ethnic communities use this plant to treat Asthma, respiratory illness, skin diseases, heart disorders, and other ailments. The main phytochemical compounds identified in different parts of the plant are sesquiterpene lactones-alantolactone and isoalantolactone. The plant is well recognized for its diverge range of biological potential such as anti-inflammatory, analgesic, antifungal, hepatoprotective, anti-allergic, adrenal beta-blocking, and cardioprotective effects. So, the present review aims to offer useful data related to phytochemistry, pharmacology, toxicity and conservation of I. racemosa. in a systematic form which will be useful for its further exploration.